Handbook of Multiphase Flow Assurance - Makogon, Taras Y.; Makogon, Taras Y. (Gulf Professional Publishing, 2019)
Handbook of Multiphase Flow Assurance allows readers to progress in their understanding of basic phenomena and complex operating challenges. The book starts with the fundamentals, but then goes on to discuss phase behavior, fluid sampling, fluid flow properties and fluid characterization. It also covers flow assurance impedance, deliverability, stability and integrity issues, as well as hydraulic, thermal and risk analysis. The inclusion of case studies and references helps provide an industrial focus and practical application that makes the book a novel resource for flow assurance management and an introductory reference for engineers just entering the field of flow assurance. - Starts with flow assurance fundamentals, but also includes more complex operating challenges - Brings together cross-disciplinary discussions and solutions of flow assurance in a single text - Offers case studies and reference guidelines for practical applications